QR Code Based Teaching Materials for Organizational Classes and Game Systems - Firmansyah, Guntur (Universitas Negeri Semarang, 2019)
To support the learning process of a course must be supported by teaching materials that are cheap, simple, easy to learn, easily accessible and quickly accessed by students. Along with the rapid advances in technology, many media have been developed both in print and online to support the learning process. One technology that is now widely known is the QR Code. This study aims to produce QR Code-based teaching materials that are easy to learn, easy and quickly accessible to improve learning motivation in organizational subjects and match systems. The research conducted is development research. The development model used is the 4D model developed by Thiagarajan, et al. 4D stages consisting of define, design, develop, and disseminate. In summary the data obtained from the evaluation of material experts showed 83%, from the evaluation of linguists 83%, evaluation of media experts 79% so it can be concluded that the product is feasible and good.